2012
DOI: 10.1093/glycob/cws126
|View full text |Cite
|
Sign up to set email alerts
|

Single amino acid exchange in bacteriophage HK620 tailspike protein results in thousand-fold increase of its oligosaccharide affinity

Abstract: Bacteriophage HK620 recognizes and cleaves the O-antigen polysaccharide of Escherichia coli serogroup O18A1 with its tailspike protein (TSP). HK620TSP binds hexasaccharide fragments with low affinity, but single amino acid exchanges generated a set of high-affinity mutants with submicromolar dissociation constants. Isothermal titration calorimetry showed that only small amounts of heat were released upon complex formation via a large number of direct and solvent-mediated hydrogen bonds between carbohydrate and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 43 publications
0
26
0
Order By: Relevance
“…These O-antigen chain shortening velocities were found irrespective of the mean chain length in the initial preparation. Accordingly, the tailspike protein alone cleaved the LPS from the O18A1 O-antigen containing strain E. coli IHE3042 [ 28 ] in the same time; however, it contained a notably higher number of short chains and had a smaller mean O-antigen chain length when compared to the host strain E. coli H TD2158 ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…These O-antigen chain shortening velocities were found irrespective of the mean chain length in the initial preparation. Accordingly, the tailspike protein alone cleaved the LPS from the O18A1 O-antigen containing strain E. coli IHE3042 [ 28 ] in the same time; however, it contained a notably higher number of short chains and had a smaller mean O-antigen chain length when compared to the host strain E. coli H TD2158 ( Figure 3 C).…”
Section: Resultsmentioning
confidence: 99%
“…HK620 has an icosahedral, symmetrical head of 59 nm width, its 38.3 kbp dsDNA genome is packed through a headful mechanism [ 26 ]. Virion structural proteins of HK620 resemble those of P22 in number and size [ 26 ], with a similar gp26 plug protein [ 27 ] and a structurally similar TSP [ 24 ] that specifically recognizes the O-antigen of its E. coli host [ 28 ]. We found that in vitro DNA release from phage HK620 was triggered by lipopolysaccharide (LPS) with a velocity similar to that found in other podoviruses.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, modifications of depolymerase could further expand its bacterial spectrum [49]. Indeed, it has been shown that even a single amino acid substitution in the active site of phage HK620 tailspike protein results in an increase of binding affinity of up to three orders of magnitude [50] and that, upon mutations, the enzyme can gain the ability to recognize other bacterial surface receptors [51]. …”
Section: Discussionmentioning
confidence: 99%
“…Within the Neisseria -PilC domain, the 3-D model also predicts binding sites for carbohydrates such as glucose (Fig 5c), previously described for tail-spike proteins for recognition and adhesion of Salmonella and E. coli bacteriophage HK620 [53].…”
Section: Resultsmentioning
confidence: 67%
“…The 3-D model of this CTD (Fig 5c) was based only on structures of the CTD of P. aeruginosa PilY1, 3hx6 [23], showing a normalized Z-score of the threading alignments, up to 7.52. Other structural analogs predicted using I-TASSER, are oxidoreductases-substrate oxidation and electron transfer (PDB: 1h4jE, 1lrwA, 2d0vI, 1yiqA1, 1FLG), with Ca 2+ or pyrroloquinoline quinone (PQQ) as ligands (see below). Within the Neisseria -PilC domain, the 3-D model also predicts binding sites for carbohydrates such as glucose (Fig 5c), previously described for tail-spike proteins for recognition and adhesion of Salmonella and E. coli bacteriophage HK620 [53]. Also within the Neisseria -PilC domain is a motif that occurs in propellers of PQQ cofactor binding domains (SMART and InterPro accession numbers SM00564 and IPR018391, respectively) of 27 aa (region 926-952) that catalyzes redox reactions; e.g.…”
Section: Resultsmentioning
confidence: 79%